Comparing laparoscopic and open umbilical hernia repair: Quality of life and outcomes - ERGENÇ, MUHAMMER (My University, 2024)
Umbilical hernia repair is a frequently conducted elective procedure in general surgery. Inde- pendent of the surgical approach used, various clinical hurdles must be successfully navigated to achieve the best possible patient outcomes with this procedure. 1 , 2 Despite the operation’s widespread occurrence, there is a noticeable absence of agreement on the most appropriate surgical approach for repairing umbilical hernias. The general consensus among surgeons is that umbilical hernias larger than 2 cm should be addressed using mesh repair, and some experts even suggest considering mesh repair for all hernias larger than 1 cm. It is commonly agreed that hernias smaller than 1 cm can be adequately managed with suture repair. However, there are opposing viewpoints, with certain professionals recommending mesh usage for umbilical hernias of all dimensions. 2-7 As with other surgeries, there are various recommendations for improving patient outcomes after surgery for patients undergoing abdominal wall reconstruction. 8-10 Challenges that demand significant attention after surgery include postoperative pain, the possibility of readmission, and complications associated with the wound, such as surgical site infections, hematoma, and the formation of seromas. In recent years, laparoscopic methods of umbilical hernia repair have gained increasing popularity. Studies indicate that this technique offers several benefits, such as a decrease in recurrence rates and fewer wound-related complications.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; Cerrahi; Surgery